Studies on the biology and management of Scarabaeidae in horticultural crops - Donaldson, Jean M. I.(Jean Margaret Isabel (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD (Agric)) -- University of Stellenbosch, 1985.